Effect of CEO Duality and Board Characteristics on the Choice of Sustainability Report Format of Listed Firms in India - Kofi Mintah Oware (Universitas Pasundan, 2022)
Stakeholders have raised concerns about how business operations affect the environment. Firms have responded through integrated reporting (financial and non-financial), which seeks to provide additional information about firm activities to improve stakeholders’ trust. This study examines the effect of chief executive officer (CEO) duality and board characteristics on the choice of the sustainability report format in India. The study uses an inclusive sample of 800 firm-year observations between 2010 and 2019. The study applies the binary probit to analyze the data from the Indian Stock Exchange. We find that CEO duality increases the likelihood of choosing integrated reporting over stand-alone sustainability reporting. This study suggests that the combined role leads to poor governance and contributes to a choice that presents less information to stakeholders. The second finding shows that independent directors are more likely to choose stand-alone reporting over integrated reporting. The study suggests that the internal policing responsibility of independent directors supports a report format that communicates more information to stakeholders. Finally, the total number of directors is insignificant in terms of the sustainability report format. Our study adds novelty to research because previous studies have only examined CEO and sustainability. However, this study is the first to investigate CEO duality and board characteristics in the choice of a sustainability report format.